2016
DOI: 10.1111/imm.12687
|View full text |Cite
|
Sign up to set email alerts
|

Co‐operative suppression of inflammatory responses in human dendritic cells by plant proanthocyanidins and products from the parasitic nematode Trichuris suis

Abstract: Interactions between dendritic cells (DCs) and environmental, dietary and pathogen antigens play a key role in immune homeostasis and regulation of inflammation. Dietary polyphenols such as proanthocyanidins (PAC) may reduce inflammation, and we therefore hypothesized that PAC may suppress lipopolysaccharide (LPS) -induced responses in human DCs and subsequent T helper type 1 (Th1) -type responses in naive T cells. Moreover, we proposed that, because DCs are likely to be exposed to multiple stimuli, the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 73 publications
4
44
0
Order By: Relevance
“…We used predetermined, moderate concentrations of each parasite antigen to ensure that we did not saturate the DC response; indeed preliminary experiments showed that higher concentrations of G. duodenalis and A. suum induced substantially more inhibition (close to 100%) of inflammatory cytokine production (our unpublished data). Moreover, we have previously demonstrated synergistic suppression of LPS‐induced IL‐6 and IL‐12p70 production by TsSP and plant polyphenols, confirming that DC activity can be simultaneously modulated by multiple external stimuli under these conditions . If the different parasite products interacted independently with DCs, by definition an additive reduction in cytokine secretion would have observed.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We used predetermined, moderate concentrations of each parasite antigen to ensure that we did not saturate the DC response; indeed preliminary experiments showed that higher concentrations of G. duodenalis and A. suum induced substantially more inhibition (close to 100%) of inflammatory cytokine production (our unpublished data). Moreover, we have previously demonstrated synergistic suppression of LPS‐induced IL‐6 and IL‐12p70 production by TsSP and plant polyphenols, confirming that DC activity can be simultaneously modulated by multiple external stimuli under these conditions . If the different parasite products interacted independently with DCs, by definition an additive reduction in cytokine secretion would have observed.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, we have previously demonstrated synergistic suppression of LPS-induced IL-6 and IL-12p70 production by TsSP and plant polyphenols, confirming that DC activity can be simultaneously modulated by multiple external stimuli under these conditions. 13 If the different parasite products interacted independently with DCs, by definition an additive reduction in cytokine secretion would have observed. Our results therefore suggest a degree of antagonism between the different parasite products, the reasons for which are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Niezen et al (2002) measured higher antibody titers against antigens to adult T. circumcincta and adult and larval T. colubriformis when lambs were fed with sulla compared with alfalfa. Moreover, recent in vitro studies have also indicated that CTs can directly modulate the activity of immune cells such as gd T cells and dendritic cells, potentially enhancing the host's innate immune response (Tibe et al, 2012;Williams et al, 2016Williams et al, , 2017. Moreover, recent in vitro studies have also indicated that CTs can directly modulate the activity of immune cells such as gd T cells and dendritic cells, potentially enhancing the host's innate immune response (Tibe et al, 2012;Williams et al, 2016Williams et al, , 2017.…”
Section: Tissue and Host Responses To Condensed Tanninsmentioning
confidence: 99%